Digital Humanities and Renaissance Studies in Canada: A Graduate Student’s Perspective - Loose, Sarah M. (Renaissance and Reformation / Renaissance et Réforme, 2014)
This article focuses on digital humanities and Renaissance studies in Canada, highlighting established projects such as Iter and newer efforts such as Serai, and addressing recent interest in historical GIS. This survey of projects demonstrates how the work of Renaissance studies faculty and graduate students in Canada is increasing accessibility to sources, creating new knowledge environments and spaces for collaboration, and encouraging new ways to map and visualize Renaissance data, with an end result that enhances our understanding of the past and the ways that digital technology is changing humanities scholarship. The article also suggests that from the perspective of graduate students, participation in these endeavours provides not only training in digital technologies but also the opportunity to contribute knowledge to the field in concrete ways and the chance to establish a foundation in methodologies and practices that will shape approaches to Renaissance studies research and teaching in the future.